DESEMPENHO DE FRANGOS DE CORTE CRIADOS EM DIFERENTES DENSIDADES DE CRIAÇÃO NA FASE DE CRESCIMENTO (22-35 DIAS) - SILVA, Eduardo Santos; OLIVEIRA, Andréia Fróes Galuci; HENRIQUE, Cleoneide dos Santos; ANDRADE, Agner de Freitas; MELLO, Bruna Finotti Fonseca Reis; BUZATTO, Lara de Oliveira (ANAIS DO ENIC, 2017)
-